2014 IEEE International Congress on Big Data 2014
DOI: 10.1109/bigdata.congress.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Dmodel: Online Taxicab Demand Model from Big Sensor Data in a Roving Sensor Network

Abstract: Abstract-Investigating passenger demand is essential for the taxicab business. Existing solutions are typically based on offline data collected by manual investigations, which are often dated and inaccurate for real-time analysis. To address this issue, we propose Dmodel, employing roving taxicabs as real-time mobile sensors to (i) infer passenger arriving moments by interactions of vacant taxicabs, and then (ii) infer passenger demand by a customized online training with both historical and real-time data. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Mining taxi trajectory data has been a research hotspot in the smart city [22]; many scholars have studied this issue. rough the analysis of relevant studies, we find that the literature on taxi research mainly focuses on two aspects.…”
Section: Related Workmentioning
confidence: 99%
“…Mining taxi trajectory data has been a research hotspot in the smart city [22]; many scholars have studied this issue. rough the analysis of relevant studies, we find that the literature on taxi research mainly focuses on two aspects.…”
Section: Related Workmentioning
confidence: 99%
“…We get a homogeneous equation set with n equations and n × n variables of Y k , which always has a feasible solution. Hence, we plug in the values of b k i = cr k i (a k i ) 0.5δ n j=1 (r k j ) 1−0.5δ to (28) to get values of X k ij .…”
Section: Appendix a Proof Of Lemmamentioning
confidence: 99%
“…In this paper, we focus on modern taxi networks, where real-time occupancy status and the Global Positioning System (GPS) location of each taxi are sensed and collected to the dispatch center. Previous research has shown that such data contains rich information about passenger and taxi mobility patterns [31], [24], [23]. Moreover, recent studies have shown that the passenger demand information can be extracted and used to reduce passengers' waiting time, taxi cruising time, or future supply rebalancing cost to serve requests [16], [25], [32].…”
Section: Introductionmentioning
confidence: 99%